Knowledge management and organizational performance of mobile service firms in Nigeria: a proposed framework - Sarkindaji, Bashir Danlami; Hashim, Noor Azmi; Abdullateef, Aliyu Olayemi (IISTE, 2014)
Over the years, knowledge management has become a major strategic necessity that organizations require to succeed in the global business atmosphere. Knowledge as one of the most vital assets of all corporate organizations must be effectively identified, acquired, stored, shared and implemented in the most profitable way that could achieve sustainable competitive advantage. This study reviews the concepts of knowledge management and organizational performance and proposes a model for further research in the area of knowledge management on performance of mobile service firms in Nigeria.The study envisages that the effect of knowledge management dimensions on organizational performance of mobile service firms in Nigeria could be mediated by technological innovation in the industry.Hence, it is recommended that mobile operators should develop and implement strategic knowledge management policy proficient to providing appropriate organizational knowledge that satisfies changing customers’ needs and preferences.